Classification Methods for Remote Monitoring in Overhead Transmission Power Lines: A Comprehensive Survey (Eurasian Journal of Engineering and Technology, 2024)
Remote monitoring plays a pivotal role in ensuring the reliability, safety, and performance of overhead transmission power lines (OTPL). The adoption of advanced classification methods enhances the efficiency of analyzing data collected through remote monitoring systems. This article presents a comprehensive review of WSN communication applied to remote monitoring data in overhead transmission power lines, offering insights into their applications, strengths, and challenges. Remote monitoring of overhead power lines serves as a solid and promising foundation for the implementation of the modern Smart grid concept.